Implementing a Positive Culture in Realizing Education Quality in Elementary Schools - Marisa, Riandi; Yulia Santi (Genderang Asa: Journal of Primary Education, 2024)
This research aims to present an exposition on the impact of school quality as a result of the implementation of a positive culture on students in elementary school, specifically at SD Negeri 5 Bireuen. The research method employed is qualitative, utilizing data collection techniques such as observation, interviews, and documentation. The results of this study indicate the routine activities conducted by the school community, particularly teachers, towards students that apply a positive culture by enforcing discipline through positive habituation activities, such as instilling self-confidence through greetings upon welcoming students at the school gate, conducting blessed gatherings, reciting prayers, inquiring about well-being in a manner that stimulates students to share enjoyable and less enjoyable experiences, singing local songs before starting lessons, participating in joint cleaning or community service at school, involving students in every school activity such as being flag ceremony officers and participating in various extracurricular competencies like scouting and arts and culture workshops, and fostering a learning community through Malim Diwa to enhance the quality of education and develop characters of self-confidence and independence in students. The learning process is based on real-life issues related to students' daily lives, which trains students to think critically in expressing ideas and concepts within the learning material. Additionally, the study encourages practical activities in the creation of art pieces and wall decorations for classrooms, based on ideas agreed upon by students, aiming to develop student creativity.